Protective Immunity against Mycobacterium tuberculosis Induced by Dendritic Cells Pulsed with both CD8(+)- and CD4(+)-T-Cell Epitopes from Antigen 85A - McShane, Helen (American Society for Microbiology, 2002)
Immunization with DNA followed by modified vaccinia virus Ankara strain, both expressing the antigen 85A, induced both CD4(+)- and CD8(+)-T-cell responses in BALB/c mice. Following challenge with Mycobacterium tuberculosis, this prime-boost regimen produced protection equivalent to that conferred by Mycobacterium bovis BCG. Following immunization with dendritic cells pulsed with an antigen 85A CD4(+)- or CD8(+)-restricted epitope, alone or in combination, copresentation of both epitopes on the same dendritic cell was required for protection, demonstrating that induced CD8(+) T cells can play a protective role against tuberculosis.